2018
DOI: 10.1051/kmae/2018020
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton diversity of drainage system reservoirs at an opencast mine

Abstract: The aim of this study was to determine the structure of zooplankton in three artificial water reservoirs, the technological function of which is to pre-treat waters from a drainage system of a brown coal open mine by removing inorganic suspension. The background for the zooplankton qualitative and quantitative analyses was the hydrochemical conditions in the individual reservoirs. The greatest zooplankton abundance (N), number of taxa (n), Shannon’s diversity (H'), and species eveness (J') was noted in reservo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 40 publications
(40 reference statements)
0
21
0
Order By: Relevance
“…Investigations initiated on the ecosystems of post‐mining reservoirs to reduce suspended matter found that the water variables, zooplankton abundance and diversity were similar to natural aquatic ecosystems (Goździejewska, Skrzypczak, Paturej, & Koszałka, ). The aim of the present study was to determine the dynamics of the zooplankton structure as an indicator of ecosystem processes in three reservoirs of the drainage system where different fishing models were applied.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Investigations initiated on the ecosystems of post‐mining reservoirs to reduce suspended matter found that the water variables, zooplankton abundance and diversity were similar to natural aquatic ecosystems (Goździejewska, Skrzypczak, Paturej, & Koszałka, ). The aim of the present study was to determine the dynamics of the zooplankton structure as an indicator of ecosystem processes in three reservoirs of the drainage system where different fishing models were applied.…”
Section: Introductionmentioning
confidence: 83%
“…All three reservoirs are of similar construction, each comprised of three functional zones (Figure ): (A) the inflow zone collects water from the separating well and facilitates gravitational sedimentation of the coarsest suspended‐matter fraction; (B) water enters the main basin of the reservoir where fine inorganic fractions are deposited; and (C) sedimentation concludes in the plant filter zone, which consists of several macrophyte species (Goździejewska et al, ). Water exits the filter zone (C) through an outflow, and the water flows from each reservoir into a common discharge canal.…”
Section: Methodsmentioning
confidence: 99%
“…The reservoirs were dominated by eurytopic Rotifera ( Polyarthra longiremis , Ascomorpha ovalis , Filinia longiseta , Keratella spp., Synchaeta spp.) that tolerate a wide range of environmental parameters and were often reported to be components of artificial, post-mining waters 1,36,4952 . Note that the concentrations of suspension did not fluctuate enough among the reservoirs to elicit environmental stress, which is important factor for the zooplankton to generate appropriate adaptive mechanisms 37,46 .…”
Section: Discussionmentioning
confidence: 99%
“…To reduce pollution and sustain required water quality, drainage water is directed to settling reservoirs prior to discharge into the rivers. Apart from this primary function, however, settling reservoirs are also used as fisheries and places for various socio-recreational activities 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation